Comparison of different extraction methods for the determination of α‐ and β‐thujone in sage (Salvia officinalis L.) herbal tea. Issue 18 (12th August 2013) - Arceusz, Agnieszka; Occhipinti, Andrea; Capuzzo, Andrea; Maffei, Massimo E.
<x xml:space="preserve">Abstract</x> Salvia officinalis L. (sage) is an important industrial plant used both for food and pharmaceutical purposes. The terpene fraction of this plant is responsible for many of its therapeutic and culinary properties. We used different extraction methods Tenax TA® purge and trap, headspace (HS) solid‐phase microextraction, HS sorptive extraction, and stir bar sorptive extraction to analyze the terpene fraction extracted from sage tea by GC–MS. Twenty compounds were identified, including α‐, β‐thujone, and several other oxygenated monoterpenes (1, 8‐cineole, linalool, camphor, boneol, and bornyl acetate) and oxygenated sesquiterpenes (caryophyllene oxide, viridiflorol, humulene epoxide I, II, and III). Tenax TA® and HS sorptive extraction extracted a lower number of identified compounds, whereas HS solid‐phase microextraction allowed the complete extraction of volatiles with particular reference to α‐ and β‐thujone. The importance of the determination of thujones content in sage herbal tea is also discussed.